Gender, sexuality and queerness in American horror story : critical essays - Earle, Harriet E. H. (McFarland & Company, Inc., Publishers, 2019)
The horror anthology TV show American Horror Story first aired on FX Horror in 2011 and has thus far spanned eight seasons. Addressing many areas of cultural concern, the show has tapped in to conversations about celebrity culture, family dynamics, and more. This volume with nine new essays and one reprinted one considers how this series engages with representations of gender, sexuality, queer identities and other LGBTQ issues. The contributors address myriad elements of American Horror Story, from the relationship between gender and nature to contemporary masculinities, offering a sustained analysis of a show that has proven to be central to contemporary genre television.